THE INFLUENCE OF ADMINISTRATIVE RECORDS AND HUMAN RESOURCE COMPETENCE ON BUDGET ABSORPTION IN CENTRAL BUTON TENGAH - Wardani, Dewi Kusuma; Sutria, Iyan (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to examine the effect of administrative records and human resource competency on budget absorption in the OPD of Central Buton Tengah. This type of research is quantitative research, data collection in this research uses primary data by distributing questionnaires to OPD employees in Central Buton Tengah. Sampling was carried out using purposive sampling technique. Data analysis in this study used multiple linear regression analysis. The amount of data in this research was 79 respondents and was processed using IBM SPSS version 25. The results of this research show that administrative records have a positive effect on budget absorption, human resource competence has a positive effect on budget absorption.